Primary Perivascular Epitheloid Cell Tumour (PEComa) of the Liver: Case Report and Review of the Literature - Jafari, A.; Fischer, H. P.; von Websky, M.; Hong, G. S.; Kalff, J. C.; Manekeller, S. (Zeitschrift für Gastroenterologie, 2013)
Purpose: Perivascular epitheloid cell tumour [PEComa] is a rare neoplasm entity, characterized by perivascular epitheloid cells with a coexpression of smooth muscle and melanocytic markers. PEComas are found in a variety of localizations, though lesions within the liver are still scarcely found. Although the majority of these tumours are recognized as benign, there are some reports about advanced and aggressive tumours even with fatal outcome. By means of this case report and literary review including other 21 published cases, potential treatment modalities concerning clinical diagnostics, therapy and the follow-up care should be discussed.Methods: The following report presents the case of a 53-year old woman with a known liver lesion, since four years under regularly sonographic controls. Finally, after a haemorrhage episode, the lesion was resected and the diagnosis found. For the literary review a systematic search for case reports published between January 1, 1999 and May 1, 2012 was performed on Pubmed.Results: The only way, till now, of confirming the diagnosis is through immunohistochemical examinations. The already published Malignancy criteria by Folpe et al. must be taken carefully in question, as there are cases of malignant behaviour, that do not exactly coincide with these.Conclusion: Primary PEComa of the liver must be treated as potential malignant and therefore a close follow-up is demanded.
Keywords: liver; PEComa; HMB 45; Angiomyolipoma; perivascular epitheloid cell